Repurposing of gallium‐based drugs for antibacterial therapy. (14th February 2014) - Bonchi, Carlo; Imperi, Francesco; Minandri, Fabrizia; Visca, Paolo; Frangipani, Emanuela
Abstract While the occurrence and spread of antibiotic resistance in bacterial pathogens is vanishing current anti‐infective therapies, the antibiotic discovery pipeline is drying up. In the last years, the repurposing of existing drugs for new clinical applications has become a major research area in drug discovery, also in the field of anti‐infectives. This review discusses the potential of repurposing previously approved gallium formulations in antibacterial chemotherapy. Gallium has no proven function in biological systems, but it can act as an iron‐mimetic in both prokaryotic and eukaryotic cells. The activity of gallium mostly relies on its ability to replace iron in redox enzymes, thus impairing their function and ultimately hampering cell growth. Cancer cells and bacteria are preferential gallium targets due to their active metabolism and fast growth. The wealth of knowledge on the pharmacological properties of gallium has opened the door to the repurposing of gallium‐based drugs for the treatment of infections sustained by antibiotic‐resistant bacterial pathogens, such as Acinetobacter baumannii or Pseudomonas aeruginosa, and for suppression of Mycobacterium tuberculosis growth. The promising antibacterial activity of gallium both in vitro and in different animal models of infection raises the hope that gallium will confirm its efficacy in clinical trials, and will become a valuable therapeutic option to cure otherwise untreatable bacterial infections. © 2014 BioFactors, 40(3):303–312, 2014